Sense-making and self-making in interdisciplinarity: an analysis of dilemmatic discourses of expertise - Cuevas Garcia, Carlos Adrian (2016)
This thesis explores the discursive environment in which the ‘interdisciplinary self’ is constructed. Interdisciplinarity is part of research policy agendas across the globe; however, there are competing and contrasting discourses about its value. On the one hand, interdisciplinarity is meant to foster innovation and to address contemporary world problems; on the other hand, it represents an intellectual and a professional risk for those who engage in it. Interdisciplinarity has become a research topic in itself, but scholars have not engaged with contemporary literature on ‘the self’ and on expertise. This limits our understanding of the individuals who engage in interdisciplinary research and how they deal with their intellectual and professional challenges. This thesis aims to fill this gap by reviewing literature on expertise and analysing 27 semi-structured interviews with researchers and administrators from a large research-oriented British university. The analysis draws on an approach that focuses on how ‘the self’ is constructed in discourse and biographical narrative, taking up but also resisting widely established meanings (e.g. what is an expert, what is worthwhile professionally, etc.). The analysis identifies in particular four ‘ideological dilemmas’ that the interviewees struggle with in their arguments about their background, their skills, and the value of their careers; namely the dilemmas of ‘openness and rigour’, ‘individualism and collectivism’, ‘disciplinary tolerance and expert prejudice’, and ‘effort and reward’. These dilemmas suggest that the ‘interdisciplinary self’ is performatively and discursively constructed in a rhetorical context in which no position can remain untroubled. Therefore associating interdisciplinary individuals with idealised traits, personalities and ‘virtues’ is not so adequate. It is suggested that ‘interdisciplinary expertise’ consists of the skills of managing these dilemmas, which may be partially but not permanently solved.